Arrhythmias and Conduction Disturbances in Children at the Department of Child Health, School of Medicine University of North Sumatra/Dr. Pirngadi Hospital Medan - Dalan Keriahen Keliat; Berlian Hasibuan; Abdullah Afif Siregar; Sahat Halim (Indonesian Pediatric Society, 1989)
A retrospective study on arrhythmias and conduction disturbances was conducted in 1986 in the Division of Pediatric Cardiology of Dr. Pirngadi Hospital, Medon. There were 106 (35.33%) cases with arrhythmias and conduction disturbances out of 300 patients studied. The most common type of arrhytmia among the patients under 5 was intraventricular conduction defects, whilst in the age group of 5-10 were sinus tachycardia and intraventricular conduction defects, and in the age group of 10-15 was first degree A-V block.Rheumatic heart diseases and VSD were the most common cardiac diseases associated with arrhythmias, where the frequency were 18.86% and 10.37%, respectively. Arrhythmias associated with several extracardiac diseases were found in 60 (56.61%). Two out of 7 cases who was rreated with antia